Optimal Convergence Rates Results for Linear Inverse Problems in Hilbert Spaces. (2nd February 2016) - Albani, V.; Elbau, P.; de Hoop, M. V.; Scherzer, O.
ABSTRACT: In this article, we prove optimal convergence rates results for regularization methods for solving linear ill-posed operator equations in Hilbert spaces. The results generalizes existing convergence rates results on optimality to general source conditions, such as logarithmic source conditions. Moreover, we also provide optimality results under variational source conditions and show the connection to approximative source conditions.